A Sensitive phage‐based capture ELISA for sub‐femtomolar detection of protein variants directly from biological samples. (23rd September 2014) - Williams, Stephanie; Schulz, Philip; Sierks, Michael R.
<x xml:space="preserve">Abstract</x> To determine the role of proteins, and in particular protein variants, in human health, it may often be necessary to quantitatively determine the concentration of a specific protein variant present in complex biological samples such as blood, cerebral spinal fluid (CSF), or tissue. Many protein variants are present only at trace levels and therefore a simple assay with very high sensitivity and reliability would greatly facilitate correlation of the presence of particular protein variants with the progression of specific diseases. We have developed a simple phage based capture ELISA system that enables femtomolar or better detection of individual protein variants directly from complex biological samples. The protocol utilizes a capture reagent that selectively recognizes a unique epitope of the protein variant and a phage based detection reagent that binds to a second epitope present in all forms of the target protein. The phage based detection reagent is essentially a self‐assembling nanoparticle consisting of several thousand coat proteins that can each be labeled to amplify the detection signal by several orders of magnitude. Here we demonstrate that we can achieve subfemtomolar detection of individual protein variants that have been implicated in neurodegenerative disease directly from complex tissue homogenates and sera. The ELISA system should facilitate identification of disease specific protein variants or other compounds even when present at trace amounts in samples including blood, CSF, saliva and urine. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:289–298, 2015